Nuclear magnetic resonance spectroscopy and infrared spectroscopy analysis of precipitate formed after mixing sodium hypochlorite and QMix 2in1. - Özgür Irmak; Ekim Onur Orhan; Kamuran Görgün; Batu Can Yaman (PLoS ONE, 2018)
BACKGROUND:Mixing sodium hypochlorite (NaOCl) with chlorhexidine (CHX) forms a brown precipitate. QMix-2in1 (QMix) was introduced as a final irrigant. Manufacturer recommends interim flushing with saline between the application of NaOCl and QMix to prevent formation of precipitation. This study assessed whether para-chloroaniline (PCA) is formed after mixing NaOCl with QMix. METHODS:Commercially available, 5.25% NaOCl solution, 2% CHX, QMix, 15% ethylenediaminetetraacetic acid (EDTA) and 98% PCA in powder form were used. Groups were prepared at room temperature. Group 1, 98% PCA in powder form; Group 2, 2% chlorhexidine (CHX); Group 3, QMix; Group 4, 5.25% sodium hypochlorite (NaOCl) mixed with QMix; Group 5, 5.25% NaOCl mixed with CHX; Group 6, 15% EDTA mixed with CHX. The precipitates were extracted and analysed with Proton Nuclear Magnetic Resonance (1H-NMR) and Infrared (IR) Spectroscopy, using PCA as an internal standard. RESULTS:No PCA was found in any of the irrigant-mixture groups tested. CONCLUSIONS:This study used the interpretation of spectral results for the amino signals of precipitate formed after mixing QMix with 5.25% NaOCl using different nondestructive analysis methods, with PCA as an internal standard (control). We conclude that mixing QMix or 2%CHX with 5.25% NaOCl does not yield free PCA.